THE ROLE OF TEACHERS AND PARENTS EFFORTS TO OVERCOME OBSTACLES LEARNING SLOW LEARNERS DURING THE PASCA COVID-19 PANDEMIC - Mauladiah; Siti Mayang Sari; Akmaluddin (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Children's learning outcomes cannot be said to be optimally successful where for slow learner children, online learning is not a good solution. this is supported by not all parents and teachers play an optimal role. This problem is one of the reasons for research which aims to examine the role of teachers and parents in overcoming the difficulties of learning mathematics in slow learner children during the Covid-19 pandemic. The research used is qualitative with the research design used is descriptive qualitative. There were 3 research subjects used by researchers, namely one mathematics teacher, one parent of a child with special needs and one school principal. Using online interviews and observation methods to collect data. The data analysis technique used is data simplification, data presentation and conclusion. The results of this study indicate that the teacher's role is that there is special treatment in class, the teacher always monitors the assignments of slow learner children and there is a mathematics learning video sent by the teacher via WhatsApp. The role of parents is as educators for their children, parents as protectors of children, parents' priority children, and parents know the child's condition when at home. The role of the principal is to guide the teacher in the learning process, through the evaluation process for the teacher. The results of this study explain that teachers, parents, and school principals have an important and influential role in overcoming the learning difficulties of slow learners.